Peranan Kepala Sekolah dalam Meningkatkan Kualitas Mengajar Guru PAI Melalui Kegiatan Supervisi Akademik di SDN Baluase Sekolah Daerah Terpencil - Wahdiyatunnisa Wahdiyatunnisa; Abdul Halim; Pahrurrazi Pahrurrazi (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the role of school principals in improving the teaching quality of Islamic Education (PAI) teachers through academic supervision activities in schools in remote areas. In this study the authors describe their research about the effect of school principals' academic supervision activities on the teaching quality of Islamic Religious Education teachers. The method used in this research is a qualitative descriptive method with a case study type of research. In accordance with the results of research in academic supervision activities, it succeeded in increasing the value of lesson planning by 37%, and the value of the implementation of learning by 28% with the results of achieving an average score of 48.57 for PAI teachers in lesson planning activities in semester I (odd), then after academic supervision activities in semester II, the value of the lesson plan increased to 85.71. This value is the average value of the seven aspects assessed by the principal in the academic supervision activity assessment sheet. Furthermore, the results achieved for the implementation of learning activities in the first semester (odd) were 46.96 and after carrying out academic supervision activities in the second semester, the value of the implementation of learning activities increased to 74.78. This value is the average value of the seven aspects assessed by the principal in the academic supervision activity assessment sheet. By looking at these results, the academic supervision activities carried out by the principal for PAI teachers were successful and could improve the quality of teaching for these teachers.